Highly active Co–Mo–C/NRGO composite as an efficient oxygen electrode for water–oxygen redox cycle. Issue 46 (11th November 2016) - Liu, Chun-Hui; Tang, Yu-Jia; Wang, Xiao-Li; Huang, Wei; Li, Shun-Li; Dong, Long-Zhang; Lan, Ya-Qian
Abstract : A metal/metal carbide-based composite (Co–Mo–C@NRGO-1) was synthesized using Co-doped polyoxometalate/conductive polymer/graphene precursors (Co-PCG) as an electrocatalyst for the water–oxygen redox cycle. Abstract : The slow kinetics of the oxygen evolution reaction (OER) and the oxygen reduction reaction (ORR) have hindered energy conversion and storage greatly. Design of a new class of low-cost and highly efficient electrocatalysts for the water–oxygen redox cycle (WORC) system including OER and ORR is considered a huge challenge. Controlled synthesis of unique and stable precursors as a perfect platform to synthesize target products with diverse compositions are of vital importance. Herein, we synthesized a metal/metal carbide-based composite (denoted as Co–Mo–C/NRGO-1) by directly carbonizing Co-doped polyoxometalate/conductive polymer/graphene precursor (Co-PCG) as an efficient bi-functional electrocatalyst. The resulting Co–Mo–C/NRGO-1 composite exhibited superior electrocatalytic activity for OER with an ultra-low Tafel slope of 42 mV dec −1, a small overpotential of 330 mV vs. RHE at the current density of 10 mA cm −2 and long-term stability in alkaline medium. The ORR performance was also investigated with a positive onset potential (∼−95 mV vs. Ag/AgCl), remarkable stability over 30 000 s and good tolerance to methanol crossover. Most importantly, the OER performance of Co–Mo–C/NRGO-1 was the best among all the reported carbide-based materials and was comparable to the best OER electrodes.